Build your Business Website without Coding Experience, A Practical Guide for UMKM - Raswati, Elsa Mundi; Putra, Muhammad Azizsyah; Lantip Nurohman; Muhammad Ghifari; Muhammad Sayyid Farhan; Rita Dewi Risanty; Mujiastuti, Rully; Rosanti, Nurvelly; Hendra; Adharani, Yana (Society : Jurnal Pengabdian Masyarakat, 2026)
In the era of Industrial Revolution 4.0, Small and Medium Enterprises (SMEs) face significant pressure to adapt to digital transformation. However, a major problem persists: many business owners lack the technical skills to build websites and perceive the process as costly and complex, leaving them reliant solely on social media algorithms. To address this gap, a community service program titled "Build Your Business Website Without Coding Experience" was implemented to assist SMEs in establishing a professional digital presence. The solution offered was a comprehensive training program combining a webinar on the urgency of frontend design with a technical workshop on template-based website management using Visual Studio Code, GitHub, and Vercel. This method allowed participants to modify and deploy websites without extensive programming knowledge. The outcomes were significant; participants showed a marked improvement in digital literacy, with average understanding scores increasing from 82.95 in the pre-test to 92.4 in the post-test. Furthermore, participants successfully deployed their own business websites, proving that this practical approach effectively lowers technical barriers and enhances SME competitiveness in the digital ecosystem.